2020
DOI: 10.1111/cas.14726
|View full text |Cite
|
Sign up to set email alerts
|

Bizarre giant cells in human angiosarcoma exhibit chemoresistance and contribute to poor survival outcomes

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…STC1 is one of the downstream genes of HIF‐1α, and the presence of HRE (hypoxia‐response element) in the promoter region of STC1 has been confirmed in previous studies 12 . It also has been reported by many literatures that STC1 expression could be upregulated by HIF‐1α in certain human tumors, 11,20–22 and is also believed to be involved in tumor development and chemotherapy resistance 23,24 …”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…STC1 is one of the downstream genes of HIF‐1α, and the presence of HRE (hypoxia‐response element) in the promoter region of STC1 has been confirmed in previous studies 12 . It also has been reported by many literatures that STC1 expression could be upregulated by HIF‐1α in certain human tumors, 11,20–22 and is also believed to be involved in tumor development and chemotherapy resistance 23,24 …”
Section: Discussionmentioning
confidence: 53%
“…12 It also has been reported by many literatures that STC1 expression could be upregulated by HIF-1α in certain human tumors, 11,[20][21][22] and is also believed to be involved in tumor development and chemotherapy resistance. 23,24 However, as a transcription factor, HIF-1α could regulate a series of downstream genes, recently researchers found that HIF-1α drives gemcitabine resistance in pancreatic cancer by modulating the transcription of IL37. 25 And STC1 transcription is not only regulated by HIF-1α, research has proved that STC1 transcription could be promoted by DROSHA to maintain the stemness of breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…The Di-Electro-Phoretic Array (DEPArray) system is a microchip-based digital sorter combining precise microfluidics and microelectronics in a highly automated platform, allowing the isolation of single cells for downstream genomic amplification and sequencing [ 145 ]. Its application, though limited in terms of scalability and high costs involved, enables the recovery of individual rare cells of interest from heterogeneous samples for detailed analysis [ 146 ]. A more cost-efficient strategy for single cell genomic analysis is to use a targeted sequencing approach for the detection of specific gene mutations and clonal structure within the tumor, achievable using the Tapestri system [ 147 , 148 , 149 ].…”
Section: Emergence Of Single-cell Technologiesmentioning
confidence: 99%
“…In the sample of angiosarcoma containing giant cells, the COL11A1 gene was overexpressed with up-regulation of immune-related metabolic stress and metastasis/matrix remodeling pathways. 73 COL11A1 was overexpressed in bladder cancer and was found to be associated with tumor invasion and metastasis. 74,75 Whole transcriptome analysis of 36 fresh osteosarcoma samples revealed that COL11A1 was involved in the development of osteosarcoma.…”
Section: Other Cancermentioning
confidence: 99%